2020
DOI: 10.1371/journal.pone.0234989
|View full text |Cite
|
Sign up to set email alerts
|

N-glycomic profiling of colorectal cancer according to tumor stage and location

Abstract: Alterations in glycosylation are seen in many types of cancer, including colorectal cancer (CRC). Glycans, the sugar moieties of glycoconjugates, are involved in many important functions relevant to cancer and can be of value as biomarkers. In this study, we have used mass spectrometry to analyze the N-glycan profiles of 35 CRC tissue samples and 10 healthy tissue samples from non-CRC patients who underwent operations for other reasons. The tumor samples were divided into groups depending on tumor location (ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
8
20
1
Order By: Relevance
“…Bi-antennary mono-galactosylated and mono-galactosylated caped with one sialic acid compositions were overrepresented in tumor samples. Curiously, these forms are not usually found increased in CRC [ 19 ]. On the contrary, MS-based studies have shown a decrease rather than increase of bi-antennary compositions, mostly bisected forms [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bi-antennary mono-galactosylated and mono-galactosylated caped with one sialic acid compositions were overrepresented in tumor samples. Curiously, these forms are not usually found increased in CRC [ 19 ]. On the contrary, MS-based studies have shown a decrease rather than increase of bi-antennary compositions, mostly bisected forms [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the current knowledge of the N-glycan profile in cancer has been based on quantification methods by LC-MS technology, such as adopted in this study, with characterization of N-glycan in a compositional level by accurate mass profiling [ 10 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 30 , 31 , 41 ]. Notwithstanding, we are aware that in-depth analysis of linkage positions and retention times of isomers or differential anomeric forms in LC/MS acquisitions, may add new insights on glycosylation as a source of biomarkers in cancer, what will surely deserve close attention in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected a study where researchers used mass spectrometry to analyze differences in N-glycan profiles between tumor and healthy samples. More details are reported in Holm et al (2020) .…”
Section: Resultsmentioning
confidence: 99%
“…As previously stated, alterations in glycosylation patterns, mediated by the modified glycosyltransferase expression, are involved in CRC malignant transformation [ 11 , 140 ]. Therefore, glycoconjugates and the molecules involved in their synthesis are interesting targets for new therapeutic approaches.…”
Section: Implications Of Glycosylation and Glycosyltransferases In Comentioning
confidence: 99%